A systematic review and meta-analysis of the serological diagnosis of Toxoplasma gondii infection highlight the lack of a One Health integrative research. (February 2023) - Huertas-López, Ana; Álvarez-García, Gema; Sánchez-Sánchez, Roberto; Cantos-Barreda, Ana; Ibáñez-López, Francisco Javier; Martínez-Subiela, Silvia; Cerón, José Joaquín; Martínez-Carrasco, Carlos
Abstract: Toxoplasma gondii is a globally distributed food-borne zoonotic parasite with numerous infection sources. The control of this zoonosis requires a One Health response that partially depends on serological monitoring in humans and animals. Herein, a systematic review and a meta-analysis were performed to analyse and compare the transdisciplinary and integrative research under the One Health approach. We searched for articles published between January 1st 2014 and September 5th 2022, focused on the development and evaluation of serological techniques for the diagnosis of T. gondii infection in humans and animals. After an exhaustive search on three scientific databases, a quality assessment was performed on 291 articles by QUADAS-2 tool, and 113 articles were finally selected. A total of 18 variables were extracted and analysed, including bibliometric characteristics, study aims and methodology. Remarkably, none of the studies included in the meta-analysis explicitly quoted the words "One Health", and only 23.9% of them alluded to the principles underlying the One Health approach; in particular, none were conducted by physician-only teams, with the majority of these studies involving interdisciplinary research teams, followed by veterinarians and by non-physician or non-veterinarian researchers. The One Health approach followed in the serodiagnosis of T. gondii still needs further integration among scientific disciplines, which is essential to design effective control strategies. Highlights: The serological diagnosis of Toxoplasma gondii infection in humans and animals was reviewed. Quality assessment showed high heterogeneity as 178/291 articles were discarded. One Health approach still needs further integration between scientific disciplines. Interdisciplinary teams implicitly suggested the need to apply the One health approach. Relevant differences between studies done on humans and animals were identified.